CONSTRUCTING TEACHER’S SELF-ASSESSMENT OF RAPPORT BUILDING IN EFL CLASSROOM - Nova, Muhamad (International Journal of Education, 2017)
A good education is not only about academics, but also the positive social interaction in classroom. Therefore, there is a need to build rapport in classroom interaction. In building rapport, EFL teachers need to conduct several activities, and through self-assessment, teachers can monitor and evaluate their own teaching for professional development. However, self-assessment instrument for building rapport has not been developed yet by any researchers. To fill the needs, this study is established to construct a self-assessment for teacher in building rapport in EFL classroom. By applying design research from a curriculum perspective, the results revealed a self-assessment instrument of maintaining rapport for EFL teacher. The Cronbach’s alpha coefficient (α = .928) of this instrument indicated high reliability and the instrument can be considered a reliable instrument to be used for the study sample. EFL teachers can do self-monitoring and self-evaluation on their rapport building in classroom interaction. Additionally, further research in investigating the effect of using this instrument in assessing teacher’s quality is required.